KECERDASAN EMOSIONAL DAN KONSEP DIRI DENGAN HASIL BELAJAR IPS - Rachmiati, Nur Izma (JURNAL PENDIDIKAN DASAR, 2016)
Abstract: The purpose of this research to determine the correlation between emotional intelligence, self-concept and learning results of social science students. This research was implemented at Elementary School East Pejaten Sub District Pasar Minggu in Grade fifth with 60 students taken by random sampling. The method of thisresearch is survey research with quantitative approach. The technique used toanalyzethe datawasthe statistical techniqueof regressionandcorrelation. The data collection instrument in test and questionnaires has been used to test validity and reliability. The findings of the research are as follow: (1) there is a positive correlation between emotional intelligence and learning results of social science students; (2) there is a positive correlation between self-concept and learning results of social science students; (3) there is a positive correlation between emotional intelligence and self-concept and learning results of social science students. The research implied that the learning results of social science students can be improved by increasing the emotional intelligence and self-concept students.Keywords: Learning Results of Social Science, Emotional Intelligence, and Self ConceptAbstrak: Tujuan dari penelitian ini untuk mengetahui hubungan antara kecerdasan emosional, konsep diri dan hasil belajar IPS. Penelitian ini dilaksanakan di Sekolah Dasar Negeri Pejaten Timur Kecamatan Pasar Minggu kelas 5 dengan 60 siswa yang diambil secara acak. Metode penelitian ini adalah penelitian survei dengan pendekatan kuantitatif. Teknik yang digunakan untuk menganalisis data adalah teknik statistik regresi dan korelasi. Instrumen pengumpulan data dalam tes hasil belajar dan kuesioner telah diuji validitas dan reliabilitasnya. Berdasarkan hasil analisis, dapat disimpulkan bahwa: (1) ada hubungan positif antara kecerdasan emosional dengan hasil belajar Ilmu Pengetahuan Sosial; (2) ada hubungan positif antara konsep diri dengan hasil belajar Ilmu Pengetahuan Sosial; (3) ada hubungan positif antara kecerdasan emosional dan konsep diri simultan eously dengan hasil belajar Ilmu Pengetahuan Sosial. Berdasarkan hasil di atas, dapat disimpulkan bahwa hasil belajar Ilmu Pengetahuan Sosial siswa dapat ditingkatkan dengan meningkatkan kecerdasan emosional dan konsep diri siswa.Kata kunci: Hasil Belajar IPS, Kecerdasan Emosional, dan Konsep Diri